PENGARUH PENAMBAHAN TEPUNG LIMBAH UDANG YANG DIOLAH SECARA KIMIAWI KE DALAM RANSUM TERHADAP KUALITAS EKSTERNAL TELUR AYAM RAS - Anwari, Rivan; Tantalo, Syahrio; Nova, Khaira; Sutrisna, Rudy (Jurnal Riset dan Inovasi Peternakan, 2018)
This study aims to determined the effect of adding various levels of shrimp waste mash in the ration by chemically processing on external quality of layer’s egg and knowing the best level of addition of shrimp waste mash by chemical processing in layer’sration. The research was conducted in June--July 2018 at henhouse laying in Tanjung Kesuma Village, District of Purbolinggo, East of Lampung Regency, Lampung Province and Laboratory of Animal Production and Reproduction, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design was completely randomized design (CRD) with 4 treatments of adding shrimp waste mash with levels (0; 6; 9; 12%) and 5 replications, so that there were 20 experimental units and each experimental unit consisted of 1 chicken. The material used in this study was 20 chickens of 50 weeks of Lohmann brown strain. The results showed that the addition of shrimp waste mash with level 0; 6; 9; 12% in the ration had no significant effect (P> 0.05) on the external quality of layer’s egg (egg weight and shell thickness), but had an influence on the consumption of ration. The ration with the addition of shrimp waste mash with a level of 12% (R3) reduced the consumption of ration, but produced relatively the same egg external quality as the control ration (R0). Keywords :Layer hen, Shrimp waste mash, Egg external quality